PERLINDUNGAN TERHADAP PEKERJA DISABILITAS BERUPA PENYEDIAAN FASILITAS KERJA PADA PERUSAHAAN - Nurul Putri Fajrianty; Fence M. Wantu; Weny Almoravid Dungga (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
This article aims to find out how the disabled workers in the existing offices and enterprises in the city of Gorontalo, which are according to the rules of the Legislative Act No. 8 of 2016 on Disabled Persons and the Law No. 13 of 2003 on Employment. The protection concerned is the protection of the rights of disabled workers due to the very vulnerable circumstances of the disabled worker in their day-to-day activities. The rights studied by the researchers are more to the fulfilment of the rights of absorption of disabled workers and also the provision of facilities and accessibility for disabled employees The method used in the writing of this paper is the juris-empirical method with the fact approach and the statue approach. Primary and secondary legal data sources based on legislative regulations as well as books related to the protection of wage rights and to fill in secondary data then conducted a session of interviews with the parties concerned. With the data analysis used is qualitative data analysis. Based on the results of this study, it can be concluded that protection for disabled workers in the city of Gorontalo has not been effective because it has not provided the facilities or aids that should be available to disabled employees.